Changes in soft tissue variable of lips following retraction of anterioir teeth- A cephalometric study - Sampath Krishna Veni; Mennattallah Elsayed; Isha S Singh; Kamal Nayan; Praveen K Varma; Moode Kaladhar Naik (Wolters Kluwer Medknow Publications, 2023)
Aim: The purpose of this study was to assess the short-term perioral soft tissue variations of the lips before and after treatment cases in 15 patients with bi-maxillary protrusion using treated lateral cephalograms who had already achieved active growth. Methodology: Fifteen pre-treatment and post-treatment lateral cephalometric radiographs of 18-25-year-old individuals with bimaxillary protrusion treated with all four 1st premolar extractions were accessed from the records. From the reference planes and landmarks, 13 horizontal, 10 vertical, and 2 angular measurements were noted. Statistical comparisons between pre-treatment and post-treatment measurements were measured by a paired t-test to assess the importance of the mean variations at the predetermined significance level. Pearson's correlation coefficient (R) was utilized to assess the strength and significance of the linear relationship between the mean differences for paired (dependent and independent) variables. Results: Pearson's correlation exhibited a noteworthy positive association between the horizontal changes in upper lip position and the horizontal changes of the upper incisor tip point (H-tU1) (R = 0.748), the upper incisor cervical point (H-cU1) (R = 0.707), the lower incisor tip point (H-tL1) (R = 0.839), and the lower incisor cervical point (H-cL1) (R = 0.767). This indicated that upper lip changes are the aftermath of the retraction of the upper and lower incisors in class I bi-maxillary protrusion malocclusion. Conclusion: Thick upper lips showed more retraction of the upper lip in correlation with retraction of the incisors as compared with thin lips. The lower incisor cervical point displayed the strongest association with lower lip retraction.